Heat conduction on pan using portable parabolic stove with addition of flat mirror - Mardwianta, Benedictus; Subarjo, Abdul Haris; wiardefan, wayan (Institut Teknologi Dirgantara Adisutjipto, 2020)
This research aims to develop the parabolic stove with addition of some flat mirrors around the parabolic mirror. It will increase the heat transfer of conduction in the pan. The parabolic itself has around and concave shape, making it suitable for concentrating solar energy. The experimental method was carried out in this research and the test was carried out in an open space with solar radiation intensities with ranging from 169.6 W/m² to 974.4 W/m². The results of heat conduction on a pan without the addition of a flat mirror generate a 105.15 Watt, addition of one flat mirror will generate a 174.82 Watt, addition of two flat mirrors will generate a 259.24 Watt, addition of three flat mirrors will generate a 342.79 Watt and addition of four flat mirrors will generate a 412.26 Watt. The heat conduction depends on the intensity of the sun caught by the reflector. If the sun intensity decreases, the surface temperature between of the outer pan wall (T1) and the inner wall temperature (T2) will decrease too.